Physical and Mechanical Characteristics of Shallow Expansive Soil due to Freeze-Thaw Effect with Water Supplement - Yanlong Li; Zili Wang; Yang Luo (Advances in Civil Engineering)
Shear strength of shallow expansive soil varies along with the depth under the freeze-thaw effect. This work investigates shear strength characteristics of shallow expansive soil by simulating the actual freeze boundary conditions of seasonal frozen areas with water supplement. An integrated approach incorporating the freeze-thaw test and direct shear test was adopted. Firstly, unidirectional freezing tests for expansive soil columns under three different freezing temperature gradients were carried out. Secondly, direct shear tests under low vertical stress were performed on the standard samples, which were prepared by using cutting rings cut the thawed expansive soil columns into nine segments along with the depth. Temperature, water content, and dry density at different depths were also investigated after the freeze-thaw process. The test results showed that, after the freeze-thaw process, the shear strength of expansive soil columns showed significant differences along with the depth and highly correlated with water content, specifically the higher water content and the lower shear strength. The minimum shear strength in the expansive soil columns occurred at the soil layer below the frozen and unfrozen zones interface. The expansive soil column’s shear strength changed most under the moderate freezing temperature gradient corresponding to the most considerable shear strength reduction. Moreover, the significant decrease in cohesion was the main reason for the shear strength reduction of expansive soil after the freeze-thaw process. These results indicate significant depth variability in shear strength of expansive soil under the freeze-thaw effect.